Analisis Perkembangan Kepribadian Individu Peserta Didik Kelas 3 di SDN 2 Kartini Kota Cirebon - Nurkholis, Nurkholis; Rizky, Oldi Dwi Maulana; Pangestu, Erlyawan; Susanto, Salwa Rianti (Innovative: Journal Of Social Science Research, 2025)
The development of individual personality in elementary school students tends to have almost the same development because in each student at Kartini 2 Public Elementary School, the educators here have their own approach which has almost the same way. Personality development in each individual student is marked by the students' courage in asking and answering questions that lead to their respective personal realms. This study has a general objective, namely to determine the various characteristics and personality development of students at SDN 2 KARTINI, Cirebon City, with this research the author can understand how students develop in the current era. The method used in this study is to apply a qualitative descriptive method by approaching through observation with interview techniques. From the results of this study, we found that educators strive to support each student's personality development by using character education.